Pengaruh Inflasi, Tingkat Suku Bunga, Rasio Profitabilitas dan Rasio Solvabilitas Terhadap Return Saham - Alfinantul Qoni’ah; Syaiful Syaiful (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This study aims to test the effect of inflation, interest rates, profitability ratios and solvency ratios on stock returns. By using a sample of 70 company samples to analyze profitability ratios and solvency ratios as well as inflation and interest rate data during the 2019-2023 period. Testing is done using multiple linear analysis. The results of the analysis state that the profitability ratio and solvency ratio affect stock returns. This research can be useful for companies to maintain company performance and investors in observing stock returns. The limitations in this study are the lack of test methods and research periods.